Analysis of the Supervisory Role of the Regional Inspectorate in the Government of Minahasa Regency - Maindoka, Varie; Kairupan, Sisca Beatrix; Bulo, Laurens L. (JR Education, 2025)
This study aims to analyze the implementation of the supervisory function of the Regional Inspectorate in Minahasa Regency. As an internal government supervisory body, the Inspectorate plays a crucial role in ensuring accountability, efficiency, and transparency in implementing public administration. Utilizing a qualitative approach with a case study method, the research explores the stages of supervision, including planning, execution, reporting, and follow-up. Data was collected through interviews with key informants, including Inspectorate officers, sub-district heads, and village officials. The study reveals significant challenges, including a limited number of auditors, inadequate competencies, and insufficient internal control mechanisms. Moreover, the level of coordination and communication between the Inspectorate and other government agencies remains suboptimal. The findings underscore the need to strengthen institutional capacity, recruit competent auditors, and enhance the internal control system to ensure effective supervision. This study contributes to the discourse on good governance practices at the regional level in Indonesia.